2002
DOI: 10.1017/s0008423902778451
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Litigators and Agenda Setting on the Supreme Court of Canada

Abstract: The expanding public policy role of high courts heightens concerns over whether societal and political inequalities affect the outcomes of litigation. However, comparative research on this question is limited. This article assesses whether status inequalities between parties and differences in the experience and resources of attorneys influence the selection of cases for judicial review in the Supreme Court of Canada. A series of statistical models reveal that governments are more likely than other parties to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…Scholars have extended several theories of U.S. judicial decisionmaking to the SCC (e.g., Flemming & Krutz 2002a, 2002b; McCormick 1993; Ostberg et al 2002; Tate & Sittiwong 1989; Wetstein & Ostberg 1999). However, no one has directly studied the role of lawyer 2 capability in the Court's decisions on the merits.…”
Section: Lawyer Capability and The Sccmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have extended several theories of U.S. judicial decisionmaking to the SCC (e.g., Flemming & Krutz 2002a, 2002b; McCormick 1993; Ostberg et al 2002; Tate & Sittiwong 1989; Wetstein & Ostberg 1999). However, no one has directly studied the role of lawyer 2 capability in the Court's decisions on the merits.…”
Section: Lawyer Capability and The Sccmentioning
confidence: 99%
“…However, no one has directly studied the role of lawyer 2 capability in the Court's decisions on the merits. Two scholars, Flemming and Krutz (2002b), do examine the impact of lawyer capability on decisions to grant leaves of appeal from 1993 to 1995. They find that prior litigation experience, as well as Queen's Counsel designation, does not increase the probability that the Court will decide to hear the case.…”
Section: Lawyer Capability and The Sccmentioning
confidence: 99%
See 1 more Smart Citation
“…designation, appellate expertise and prior success on the merits in SCC litigation all help explain the degree to which lawyers participate in leaves to appeal. Two SCC studies of the impact of lawyer capability on decisions to grant leaves found little evidence of the impact of lawyer experience or QC designation on the Court 's decision~Flemming, 2004;Flemming and Krutz, 2002!. However, more recently, Szmer and colleagues~2007!…”
Section: Lawyer Capability On the Ussct And The Sccmentioning
confidence: 99%
“…Unlike his study, we focus on patterns of behavior that extend beyond majority opinion authorship, and we also utilize a more appropriate analytical approach that employs a test of statistical significance. Our study also follows the lead of prior work by Tate and Sittiwong (1989), Flemming and Kurtz (2002), and Wetstein and Ostberg (1999) by focusing attention on the Canadian Court to examine hypotheses and claims developed in the U.S. Supreme Court setting. Here we analyze the existence of acclimation affects on the Canadian Supreme Court during the Laskin, Dickson, and Lamer Court tenures (1974–1999).…”
Section: Literature Reviewmentioning
confidence: 99%